2023
DOI: 10.1001/jamaoto.2023.1573
|View full text |Cite
|
Sign up to set email alerts
|

Oral Human Papillomavirus Prevalence and Genotyping Among a Healthy Adult Population in the US

Abstract: ImportanceIn the US, oropharyngeal cancer, predominantly caused by high-risk (HR) human papillomavirus (HPV) infection, is the most frequent HPV-associated cancer, surpassing cervical cancer. However, little is known about oral HPV prevalence and genotype distribution in the general population.ObjectiveTo assess oral HPV prevalence and factors associated with HR and low-risk infection in a general US population.Design, Setting, and ParticipantsPROGRESS (Prevalence of Oral HPV Infection, a Global Assessment) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…An oral HPV prevalence of 0.7% has been observed. A substantial variability has been reported ranging from 0.3% in Italy in healthy adults [ 46 ] to more than 10% [ 3 , 45 , 47 , 48 ], with an overall value of 7.7% reported by a meta-analysis conducted in 18 years and older healthy males and females [ 12 ]. This variability has been attributed to differences in the study populations, geographic variations, methods of collection of specimen and HPV detection, and in the investigated HPV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…An oral HPV prevalence of 0.7% has been observed. A substantial variability has been reported ranging from 0.3% in Italy in healthy adults [ 46 ] to more than 10% [ 3 , 45 , 47 , 48 ], with an overall value of 7.7% reported by a meta-analysis conducted in 18 years and older healthy males and females [ 12 ]. This variability has been attributed to differences in the study populations, geographic variations, methods of collection of specimen and HPV detection, and in the investigated HPV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HPV + OPSCC are generally younger than those with HPV(-) OPSCC [ 14 ], although an increase in elderly patients has been reported [ 19 21 ]. A recent study on a cohort of over 3000 healthy adults in the United States reported that oral HPV DNA is most prevalent in older males aged 51–60 years [ 22 ]. An earlier study also reported that males aged 60–64 years had higher oral HPV prevalence compared to younger age groups [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PROGRESS (Prevalence of Oral HPV Infection, a Global Assessment) trial examined 3196 healthy adults, aged between 18 and 60 years, who visited dental clinics. The study revealed an oral HPV prevalence of 6.6% with a 2% prevalence for hrHPV [ 62 ]. This translated to 9.1% of men and 4.6% of women having any oral HPV (aHPV) infections.…”
Section: Introductionmentioning
confidence: 99%